Free Voluntary Reading and Comprehensible Input. Issue 39 (2019) - Patrick, Miriam
Abstract : Three and a half years into my journey of using Comprehensible Input and leaving the textbook behind, I started doing research on Free Voluntary Reading. As a child, I had greatly enjoyed reading and it was something my students had a hard time grasping. Similarly, my own brother nearly stopped reading all together when his school adopted the Accelerated Reader program, which assigns points for reading and testing on books. His love for reading was later reignited when, as a family, we started reading the Harry Potter series. I want my own students to have a similar experience and enjoy reading.